ANALISIS MOTIVASI BELAJAR MAHASISWA CALON GURU SEKOLAH DASAR (PGSD) PADA MATA KULIAH KONSEP DASAR IPA - yulia (Elementa: Jurnal Pendidikan Guru Sekolah Dasar, 2019)
Motivation is one of the main factors that influence success or failure in learning and teaching. One approach that can be used to determine the level of student learning motivation is the ARCS model. The four aspects that form part of the motivation are aspects of attention, relevance, confidence, and satisfaction. The purpose of this study was to determine the level of motivation to learn PGSD undergraduate students at Universitas Islam Raden Rahmat Malang in the Basic Concept of Science. This type of research is quantitative descriptive with survey methods, in this case using student motivation questionnaires. The research subjects consisted of four classes with a total of 76 students at the PGSD and PGMI Universitas Islam Raden Rahmat Malang. The results showed that the learning motivation of students candidate of basic school in the aspects of attention and relevance was in a sufficient category while for aspects of confidence and satisfaction were in the high category. However, student learning motivation in the Basic Conceptual Science course subject still needs to be improved.